2013
DOI: 10.1111/nep.12045
|View full text |Cite
|
Sign up to set email alerts
|

Role of interstitial inflammation in the pathogenesis of polycystic kidney disease

Abstract: The authors provide a comprehensive overview of our current understanding of the role of inflammation in the pathogenesis of polycystic kidney disease. In particular, the involvement of monocytes/macrophages and other infiltrating cells such as dendritic cells, T cells and other leukocytes are highlighted. ABSTRACT:Interstitial infiltrates, consisting of macrophages and other inflammatory cells, have been consistently reported in human and animal models of polycystic kidney diseases (PKD). However, the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 150 publications
1
72
0
Order By: Relevance
“…Since NF-κB regulates the transcription of TNFa and CCL2 [17] , and as the cytokine products of these genes are commonly found in models of PKD [8] , we sought to…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since NF-κB regulates the transcription of TNFa and CCL2 [17] , and as the cytokine products of these genes are commonly found in models of PKD [8] , we sought to…”
Section: Discussionmentioning
confidence: 99%
“…The non-canonical pathway is known to be stimulated by fewer stimuli (e.g., CD40 ligand and lymphotoxin-β2 [16] ) and usually implicates the RelB:p52 dimer in mediating lymphoid organ development [13,16] . There is an overlap between NF-κB-regulated genes and the pathophysiological features of PKD, such as inflammation (e.g., TNFa, CCL2), cell growth (e.g., cyclin D1), apoptosis (e.g., Bcl-xL) and hypertension (e.g., ANGII) [8,9,12,17,19] . These commonalities provide a theoretical basis for the involvement of NF-κB in PKD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other serum and laboratory factors have been associated with various aspects of ADPKD severity, including serum uric acid, HDL, fibroblast growth factor-23, collagenderived peptides, NGAL, IL-8, and TNFa. 78,[86][87][88][91][92][93][94] Although some of these factors may contribute to ADPKD progression, confirmation in additional studies is required as well as biomarker validation. …”
Section: Serum Copeptin Levelsmentioning
confidence: 99%
“…These mutations are initiator cysts formation and progression of disease (Zoja et al., 2014). Some of the pro‐inflammatory factors are identified in cyst fluid or urine samples of PKD patients (Ta, Harris, & Rangan, 2013). Recently, it has been shown that inflammation and cytokine signaling play a significant role in PKD pathogenesis.…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%